Sistem Informasi Kearsipan untuk Meningkatkan Kualitas Pelayanan - Dessy Irmawati; Yuniar Indrihapsari (Faculty of Engineering, Universitas Negeri Yogyakarta, 2014)
This study established a system to implement Visual Basic 6.0 and the MySQL database for archives management that are effective and efficient in accordance with the needs of the administrative system in the Department of Electronics Engineering Education, Faculty of Engineering, YSU. Microsoft Visual Basic 6.0 is a software that is able to be applied on windows xp, vista, windows 7, or operating systems that are commonly used in offices. The application will be able to store the presence data of lecturers, incoming mails, outgoing mails, and the biodata of lecturers. In addition, with the crystal report, the system is able to print the archive reports, to search archives, and with the tools provided by Microsoft Visual Basic 6.0, it can be made into an installer application that can be run on other computers without having to reset the MySQL database.